2020
DOI: 10.1111/1475-679x.12291
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of M&A Antitrust

Abstract: Antitrust regulators play a critical role in protecting market competition. We examine whether the political process affects antitrust reviews of merger transactions. We find that acquirers and targets located in the political districts of powerful U.S. congressional members who serve on committees with antitrust regulatory oversight receive relatively favorable antitrust review outcomes. To establish causality, we use plausibly exogenous shocks to firmpolitician links and a falsification test. Additional find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The situation is different for firms contributing to a politician who is challenging an SEC‐influential incumbent. A challenger who wins the election is unlikely to serve on an SEC‐influential committee immediately, and if appointed to one of these committees immediately, is unlikely to exert influence as a new member of the committee (e.g., Levitt and Poterba 1999; Mehta et al 2020). In either case, the election of a challenger is not likely to result in a meaningful change in the firm's connection to an SEC‐influential politician.…”
Section: Prior Research and Hypothesesmentioning
confidence: 99%
“…The situation is different for firms contributing to a politician who is challenging an SEC‐influential incumbent. A challenger who wins the election is unlikely to serve on an SEC‐influential committee immediately, and if appointed to one of these committees immediately, is unlikely to exert influence as a new member of the committee (e.g., Levitt and Poterba 1999; Mehta et al 2020). In either case, the election of a challenger is not likely to result in a meaningful change in the firm's connection to an SEC‐influential politician.…”
Section: Prior Research and Hypothesesmentioning
confidence: 99%
“…Too much discretion may be left to governments, parliaments and local autorithies to favor certain interest groups, possibly under the umbrella of some sort of immunity that exclude these bodies from the investigation and possible prosecution by the NCA (Fox & Webb, 2013). Lax rules and lack of monitoring leave room for government capture by lobbies and consequently ad hoc attempts to influence the NCA on behalf of special interests, thus weakening its ability to hinder anti-competitive actions and undermining the perception of its institutional independence (Mehta, Srinivasan, & Zhao, 2020). More in general, dysfunctionalities in important regulatory areassuch as financial, labour, environmental regulations, and so onfuel negative credibility externalities on CP enforcement.…”
Section: The Boundary Conditions For the Relation Between Competition...mentioning
confidence: 99%
“…However, in our setting, poor underlying state or district economic conditions may affect both congressional reelection prospects and local government incentives to ensure funds are properly used and controlled. Mehta, Srinivasan, and Zhao [2020] use politician transfers from Judiciary committees to more powerful committees to identify variation in the ability of corporations to obtain political influence. Because committee transfers do not affect a congressional member's link to his or her constituency, such an approach is not feasible in our setting.…”
Section: Identificationmentioning
confidence: 99%
“…Instead, our findings suggest that powerful congressional members can rely on their ability to allocate resources to their constituents to obtain reelection. 7 Researchers have shown that corporate political connections are associated with higher profitability (Amore and Bennedsen [2013]) and receipt of government contracts (Tahoun [2014]), reduced likelihood of facing IRS tax audits and SEC investigations for financial misconduct (Hunter and Nelson [1995], Correia [2014]), higher firm-specific investment (Wellman [2017]), more favorable accounting standard setting outcomes (Ramanna [2008]), greater propensity to hire a Big N auditor (Guedhami, Pittman, and Saffar [2014]), financing choices (Tahoun and van Lent [2018]), and better merger antitrust review outcomes (Mehta, Srinivasan, and Zhao [2020]). Two papers that document costs of political connections are Leuz and Oberholzer-Gee [2006] and Bertrand et al [2018].…”
Section: Introductionmentioning
confidence: 99%